How remarkable women lead - Barsh, Joanna; Cranston, Susie (Tantor Media, Inc., 2012)
Based on five years of proprietary research, How Remarkable Women Lead speaks to you as no other book has, with its hopeful outlook and unique ideas about success. It's the new "right stuff" of leadership, raising provocative issues such as whether feminine leadership traits (for women and men) are better suited for our fast-changing, hyper-competitive, and increasingly complex world.In this book, McKinsey & Company consultants Joanna Barsh and Susie Cranston establish the links between joy, happiness, and distinctive performance with the groundbreaking model of Centered Leadership.The book's personal stories and related insights show you the magic that happens when you put the five elements of Centered Leadership-meaning, framing, connecting, engaging, and energizing, to work. They include:How Alondra de la Parra built on her strengths and passions to infuse her life with meaning and make her way in the male-dominated world of orchestra conductingHow Andrea Jung, the CEO of Avon, avoided a downward spiral when the company turned down by "firing herself" on Friday and re-emerging on Monday as the "new" turnaround CEOHow Ruth Porat's sponsors at Morgan Stanley not only helped her grow but were also her ballast for coping with difficult personal and professional timesHow Eileen Naughton recovered after losing her dream job, landing on her feet at Google and open to a new leadership opportunityHow Julie Coates of Woolworth's Australia makes energy key to her professional success, with reserves for her "second shift" as wife and motherHow Remarkable Women Lead is both profoundly moving and actionable. No matter who you are, this book will help you attain a practical plan for breaking through at both work and in life.